Profit Management and Tax Avoidance on Company Value - Pangemanan, Cindy Olivia; Prasetyo, Ridho Jun; Handayani, Lilik (International Journal of Business and Applied Economics, 2024)
The purpose of this study was to analyze the effect of Profit management and tax avoidance on the value of the company. The sample consisted of 28 companies with the retrieval technique using purposive sample technique in the health, transportation infrastructure, and logistics sectors listed on the IDX for 2018-2022. The results of the study state that company value is not influenced by Profit management while company value is influenced by tax avoidance.